1955
DOI: 10.1139/v55-182
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Studies of Ligninsulphonates: Ii. Behavior as Polyelectrolytes

Abstract: Conductivity, dyestuff adsorption, and viscosity measurements on aqueous solutions of fractionated ligninsulphonate samples having various molecular weights indicate that they behave as flexible polyelectrolytes. There is evidence that ligninsulphonates of nlolecular mcight less than 5000 associate in solution in a manner analogous to rnicelle formation in colloidal electrolytes. From t h e variation of intrinsic viscosity with molecular weight, it may be collcluded that the degree of molecular branching of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1955
1955
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…The ultrafilter developed for the purpose of fractiollatillg the ligninsulphonates is described in detail in a separate publication (8); six ultrafilter cells each having a membrane area of 200 sq. cm.…”
Section: Ultrafiltrationmentioning
confidence: 99%
See 3 more Smart Citations
“…The ultrafilter developed for the purpose of fractiollatillg the ligninsulphonates is described in detail in a separate publication (8); six ultrafilter cells each having a membrane area of 200 sq. cm.…”
Section: Ultrafiltrationmentioning
confidence: 99%
“…The conceiltration ci(t) of a fraction i in the solution after a period of ultrafiltration t can be calculated from an equation derived elsewhere (8):…”
Section: Degree Of Fractionationmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus to improve LS based products, their solution behavior and the interactions between their different polymer chains must be better understood. Gardon and Mason (1955) were the first who suggested based on conductometric studies that LS may aggregate. Benko (1961a,b) found that the molecular weight (MW) of spent sulphite liquor (SSL) measured by a diffusion method increased during spray drying as a function of temperature.…”
Section: Introductionmentioning
confidence: 99%